PERSPECTIVES AND DIRECTIONS OF DEVELOPMENT OF ORGANIZATIONAL CULTURE IN THE DIGITAL AGE - Gordana Nikcevic\'; Djordjije Pavicévic\' (Agora International Journal of Economical Sciences (AIJES), 2024)
In the conditions of the strong development of digital technologies, the business of organizations in a traditional environment becomes very tight. New digital technologies have implications for modern business operations. Digital trends require changes not only in the way business organizations work (jobs, workplaces and employees) but also a change in the entire concept of organizational culture (behavior and thinking of employees). In order for digital technologies not to become an obstacle to the business of modern organizations, in our work we will identify a new organizational culture that is able to support new technologies. At the same time, we will look at the key elements of the traditional organizational culture, which we have to transform. In the final part, with the aim of improving the business of business organizations, guidelines will be given for the development of a new digital organizational culture that will contribute to the improvement of business, all in the context of adapting to new digital technologies. In the study of digital transformation and organizational culture, the authors employ analytical and synthetic approaches to achieve a deeper understanding. The analytical approach deconstructs elements through qualitative analysis, while the synthetic approach integrates information and theories to form a comprehensive concept. These approaches enable the identification of optimal strategies for different contexts, which is crucial for this study. Overall, the study contributes to theoretical understanding of digital transformation and organizational culture, while also offering practical guidance for organizations undergoing the process of digital transformation.
Keywords: 330